Forecasting future needs in English for Specific Purposes curriculum: A Delphi study among industry experts and ESP practitioners - Solihat, Dadang; Fadhly, Fahrus Zaman (Universitas Islam Sultan Agung, 2025)
This study explores future-oriented curricular priorities for English for Specific Purposes (ESP) by employing a three-round Delphi method involving 25 experts from academia and industry. In Round 1, participants identified 63 emerging themes across five domains: digital literacy integration, interdisciplinary ESP content, soft-skill infusion, task-based learning models, and adaptive assessment strategies. Round 2 consolidated and ranked 12 core components, with AI literacy, adaptive task-based modules, cross-cultural pragmatics, and soft-skills integration emerging as top priorities. By Round 3, consensus (≥75%) was achieved on a four-pillar ESP framework: technological integration, learner-centered pedagogy, discipline-specific authenticity, and outcome-based assessment. Cross-sectoral analysis revealed a significant gap between industry-driven priorities (e.g., real-time communication) and academic emphasis (e.g., critical reading and writing), highlighting the need for curricular harmonization. The findings underscore a shift toward integrative, technology-enhanced, and professionally aligned ESP models. Implications include the urgent need to reform teacher training to address competencies such as AI, sustainability, and data-driven instruction